Cardiac PET and PET/CT imaging - Di Carli, Marcelo F.; Lipton, Martin J.; SpringerLink (Online service) (New York, NY : Springer Science+Business Media, LLC, 2007)
Presents up-to-date information on the practice of cardiac PET and hybrid PET/CT. Each chapter takes a step-by-step approach, from basic principles of instrumentation, imaging, and protocols to advanced discussions of current and future clinical applications. Coverage also includes a perspective on other emerging imaging modalities, such as MRI, and the relative role of each. In addition, the volume details the technical aspects of cardiac PET and PET/CT imaging. A library of original cases completes the text by illustrating interpretation and technical challenges in cardiac PET and hybrid PET/CT.
Includes bibliographical references and index.
Keywords: Heart -- Imaging; Tomography, Emission; Medicine & Public Health; Cardiology; Diagnostic Radiology; Imaging / Radiology; Nuclear Medicine